Analisis pelaporan pengelolaan keuangan desa (Studi kasus di Desa Wuwuk, Kecamatan Tareran, Kabupaten Minahasa Selatan) - Rompas, Yiska Fira; Walandouw, Stanley Kho; Lintong, Diana Nova (Riset Akuntansi dan Portofolio Investasi, 2025)
Village financial management reporting is vital for ensuring accountability and transparency in public fund use. This study analyzes the implementation of financial reporting in Wuwuk Village, Tareran Sub-district, South Minahasa Regency, based on Minister of Home Affairs Regulation No. 20 of 2018. Using a qualitative case study approach, data were collected through interviews, observation, and documentation. The results show that the village prepares implementation and realization reports as part of the APBDes realization report. However, reporting is conducted per disbursement stage instead of per semester, causing delays due to incomplete data. These findings highlight procedural inconsistencies and limited understanding among village officials, underscoring the need for stronger administrative capacity to enhance transparency and accountability.